Analysis of Factors that Affect the Length of Job Search for Educated Workers in West Lombok Regency - Nova Junilasari; Helmy Fuadi; Eka Agustiani (Westscience Press, 2024)
This research aims to analyze the influence of wage level, education level, age, gender, and job training on the length of time looking for work for educated workers in West Lombok Regency. This research uses a type of research, namely qualitative with secondary data. Data obtained from SAKERNAS in 2023. The amount of data obtained was 200 educated workers. The analytical tools used are multiple linear regression, coefficient of determination test (R2), partial significance test (t test) and simultaneous significance test (f test). The results of this study show that the variables of wage level, education level, age, gender and job training simultaneously do not have a significant effect on the length of looking for work. Meanwhile, the R2 value is 0.026, this means that 2.6% of the length of time looking for work for educated workers is influenced by variables above which the remainder is influenced by other variables outside this research.